Pressure ulcers risk assessment tools - T. Szewczyk, Maria; Cwajda, Justyna; Cierzniakowska, Katarzyna; Stodolska, Alina; Ślusarz, Robert (Przewodnik Lekarza/Guide for GPs, 2005)
Pressure ulcers are a type of chronic wounds. This problem concerns patients with chronic illnesses and people with a number of risk factors. Chronicity of pressure ulcers and difficulties of therapy contribute to constant development of many prevention methods based on European and international prevention and treatment standards. Important part of these standards is process of patients identification in aspect of pressure ulcers development. Main role play assessment tools based on point scales evaluating the most important risk factors of pressure ulcers development.